Chapter Introduction The judicialisation and politicisation of sacrifice - Berti, Daniela (Taylor & Francis, 2024)
The introduction focuses on the issues raised by the debate on animal sacrifice over the centuries, both in the West and in South Asia. Not only did the current Indian judicial system evolve from the British colonial legacy, but internationally, many current arguments on the protection of animals call upon Indian religious and philosophical concepts as well as Western notions and values. The recent judicialisation of these debates has led to the emergence of new questions, worldwide, concerning the legal status of animals and focusing particularly on animal sacrifice and ritual slaughter. In South Asia, animal sacrifice was criticized over the centuries by sectarian and devotional movements, but these criticisms gained new impetus from the actions of Christian missionaries who projected onto India the opposition between religio and superstitio used by the first Christian writers in rejecting animal sacrifices in ancient Rome. This had a profound impact on nineteenth-century Hindu reformist leaders who also took a stand against animal sacrifice. This aspect of the debate has been taken up by Indian judges, some of whom take a spiritualistic approach to religion and are pushing for Hindu religious reforms.